Szkoła Juliusza Nowaka-Dłużewskiego. Powinowactwa historycznoliterackie - Podgórski, Wojciech J. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Juliusz Nowak-Dłużewski (31.03.1893, Goszcza – 19.04.1972, Warszawa), a literary scholar and historian, a teacher in secondary schools in Kielce and Warszawa. He did Polish Studies and his PhD in 1932 at the Jagiellonian University in the care of his promoter, Professor Ignacy Chrzanowski. During World War II he lectured at Kielce branch of Polish Studies of University of Western Lands. After the war he habilitated in Toruń on the basis of his monograph dedicated to priest Stanisław Konarski, afterwards, he took a job as a substitute for a Professor at Catholic University of Lublin and as an associate professor at University of Warsaw. His teaching and pedagogic service bore fruit in 1938 in the form of the Gold Cross of Merits. Post-war frameworks of reconstruction and the effort of the preservation from destruction of post-courtly collections from the position of the director of the National Museum in Kielce resulted in the Order of Polonia Restituta (1963). Finally, Nowak-Dłużewski’s research and development works met with recognition from the jury of the Włodzimierz Pietrzak Literary Award two times (1964, 1967). The memoir dedicated to Professor J. Nowak-Dłużewski develops from his student’s conviction about the perfection of his didactic and educational mission performed by him with devotion during the difficult times when Communism was on the rampage. We experienced Professor’s special care and foresight in the last decade of his life (1962-1972), when he resolved to “remake us into angels” by destining us for creative work in conditions close to monastic closure – in the team of a PhD seminary. A doubtless protagonist of the given text is our Master, Professor Juliusz Nowak-Dłużewski. For this reason, the references include only articles and utterances of particular people with the intention of underlining our interpersonal master-pupils bond. To my mind, this aspect appears to excuse the author in the eyes of Colleagues as well as Readers.
Juliusz Nowak-Dłużewski's School. Historical-Literary Connections
Keywords: Nowak-Dłużewski Juliusz; historia literatury polskiej; dydaktyka szkoły wyższej